Population Pharmacokinetic Modeling of a Desmopressin Oral Lyophilisate in Growing Piglets as a Model for the Pediatric Population - Gasthuys, Elke; Vermeulen, An; Croubels, Siska; Millecam, Joske; Schauvliege, Stijn; van Bergen, Thomas; De Bruyne, Pauline; Vande Walle, Johan; Devreese, Mathias (Frontiers in Pharmacology, 2018)
Desmopressin is used to treat primary nocturnal enuresis in children. Over the years, various formulations of desmopressin were commercialized of which the sublingual melt tablet is preferred in the pediatric population, despite the lack of full PK studies in this population. A full PK study was performed in growing conventional piglets to evaluate if this juvenile animal model can provide supplementary information to complement the information gap in the pediatric population. A desmopressin sublingual melt tablet (120 µg) was administered to 32 male piglets aged eight days, four weeks, seven weeks and six months (each group n = 8). Population PK (pop-PK) analysis was performed to derive the PK parameters, the between- and within-subject variabilities and the effects of covariates. Desmopressin demonstrated two-compartmental PK, with a dual, sequential absorption process, and linear elimination. Body weight was the only significant covariate on clearance and on apparent volume of distribution of the central compartment. In human pediatric trials, no double peak in the absorption phase was observed in the plasma concentration-time curves, possibly due to the sparse sampling strategy applied in those pediatric studies. Therefore, it is recommended to perform additional studies, based on the sampling protocol applied in the current study.